THE DRY BEAN IN SOWING STRUCTURE IN THE VOIVODINA PROVINCE - Bosnjak, Danica; Vasic, Mirjana (Economics of Agriculture, 2006)
In this paper harvested areas under the dry bean in the period 1954-2003 has been analyzed. An analysis covers the wole period, but also certain decades of analyzed period. Dry bean has been cultivated on average area of about 8,000 ha. That is 0.5% of total provinces arable area and about 10% of area under vegetable production. The family farms, which cultivate dry bean on the average area of the about 7,550 ha have the dominate role in the organization of the production. Their participation in the total area is 92% and thus these farms give main feature of dry bean production in Voivodina Province. Harvested areas under the drz bean in Voivodina are characterized by significant stability. That is on the first place consequence of the high stability of the family farms area. Taking into consideration agro technical characteristics of this crop and the fact that domestic supply does not meet needs of domestics consumers can conclude that rate of growth of 1.48% which was established in the last decade of analyzed period is not satisfactory.